The impact of natural disasters on economic growth - Eduardo A. Cavallo; Oscar Becerra; Laura Acevedo (Inter-American Development Bank (IDB), 2021)
This paper estimates the impact of catastrophic natural disasters on economic growth using an event study methodology on a country panel dataset from 1970 to 2019. The severity of the events is determined by the associated mortality. We find that affected economies-which, given the way natural disasters are ranked, comprise mainly developing countries-suffer an average loss between 2.1 and 3.7 percentage points (p.p.). The estimated loss is not offset by above-average growth rates in the disaster's aftermath. In contrast, when the severity of the events is determined by physical intensity rather than by mortality-which implies a more balanced estimating sample of developed and developing economies-the estimated effects on growth are negligible. Thus, the negative impacts of natural disasters on economic growth are larger for poorer countries, suggesting that the impact of natural disasters on growth is an economic development issue.
Keywords: Q54; O47; 330; Natural disasters; Economic growth; Event study